The Effect of Temperature Pressure on Multiantagonists Streptomyces sp., Tricho-derma sp. Biological Control of Fusarium oxysporum Wilt Pathogens - Penta Suryaminarsih; Dita Megasari; Tri Mujoko (Nusantara Science and Technology Proceedings)
Climate change due to global warming can increase soil temperatures. The increase in soil temperature can be influenced by air temperature which can affect the life of soil microorganisms. Streptomyces sp. and Trichoderma sp. is a soil microorganism that acts as a Biological Control Agent (APH) of plant pests and diseases. This study aims to determine the inhibitory ability of Streptomyces sp. and Trichoderma sp. at high temperature against Fusarium sp. causes of wilt disease in chilies. This research used factorial completely randomized design. The first factor is room temperature 29-31 ° C, temperature 50 ° C, and temperature 70 ° C. The second factor is the type of andosol soil (UPN land) and regusol (Pare village land). Observations were made on the number of colonies of Streptomyces sp. and Trichoderma sp. as well as inhibition against the fungus Fusarium sp. The results showed that the multiantagonist inhibition of Streptomyces sp. and Trichoderma sp. against F. ox-ysporum at 70 ° C in 90% andosol soil and the lowest at 70 ° C on 31% regusol soil.